2001
DOI: 10.1021/ja015867r
|View full text |Cite
|
Sign up to set email alerts
|

Dimerizable Cationic Detergents with a Low cmc Condense Plasmid DNA into Nanometric Particles and Transfect Cells in Culture

Abstract: The size of condensed DNA particles is a key determinant for in vivo diffusion and gene delivery to cells. Gene molecules can be individually compacted by cationic thiol detergents into nanometric particles that are stabilized by oxidative conversion of the detergent into a gemini lipid. To reach the other goal, gene delivery, a series of cationic thiol detergents with various chain lengths (C(12)-C(16)) and headgroups (ornithine or spermine) was prepared, using a versatile polymer-supported synthetic strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
154
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(162 citation statements)
references
References 26 publications
(48 reference statements)
5
154
1
1
Order By: Relevance
“…Dauty et al 35 reported a dimerizable cationic detergent, which contains free thiol, amine and alkyl groups. This alkylated ornithinyl cysteine derivative forms a complex with plasmid DNA.…”
Section: Lipid-mediated Gene Deliverymentioning
confidence: 99%
“…Dauty et al 35 reported a dimerizable cationic detergent, which contains free thiol, amine and alkyl groups. This alkylated ornithinyl cysteine derivative forms a complex with plasmid DNA.…”
Section: Lipid-mediated Gene Deliverymentioning
confidence: 99%
“…To overcome the skeletal barrier, some viruses such as SV40 activate tyrosine kinase-induced signaling cascades that lead to the local dissociation of filamentous actin. Because macromolecule-sized solutes with a gyration radius (R G ) up to 30 nm are freely diffusible in the cytoplasm (7), strategies to increase DNA mobility, such as DNA compaction into spherical 30 nm-particles (37) and active transport of the DNA toward the nucleus, are predicted to enhance the efficiency of transgene delivery (38,39). In summary, using the complementary fluorescence techniques of FCS and photobleaching, we have established a quantitative mechanism for the reduced translational diffusion of large, non-complexed DNAs in cell cytoplasm and identified the actin cytoskeleton as a new barrier for non-viral gene delivery.…”
Section: Characterization Of Dna Fragments Containing a Singlementioning
confidence: 99%
“…The large transfection increase observed between decane, dodecane and tetradecane gemini lipids tended to culminate for tetra-and hexadecane lipids. 10 In order to further explore the structureactivity relationship, we introduced some variations in the structure of the detergent, using another DNA-binding head group (spermine; C 14 CSper) or an unstable ester bond in place of an amide (C 14 oCOrn). The highest transfection activity was found with the C 14 oCOrn derivative (Table 1) and correlates with the apparition of a supramolecular organization similar to that of Transfectam.…”
Section: Gene Delivery To Cells In Culturementioning
confidence: 99%
“…C 14 COrn, C 14 CSper and C 16 COrn were synthesized as previously described. 10 The syntheses of C 14 oCOrn and DPPE-PEG 3400 (lipid-PEG) will be reported elsewhere. Lissamine rhodamine B-DPPE (lipid-Rhodamine) was from Molecular Probes (Eugene, OR, USA).…”
Section: Poly(ethylene Glycol)-coated Monomolecular Plasmid Dna Partimentioning
confidence: 99%
See 1 more Smart Citation